2019
DOI: 10.3329/bhj.v34i1.41905
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Prevalence of Dyslipidemia among Patients with Acute Coronary Syndrome Admitted in a Tertiary Level Hospital

Abstract: Background: The leading cause of mortality in men and women worldwide is coronary artery disease (CAD). For hospitalization in our country, acute coronary syndrome (ACS) is a major reason. Dyslipidemia is found one of the most important modifiable risk factors for CAD. Aim: The aim of the study was to determine the pattern and prevalence of dyslipidemia among patients with ACS admitted in National Institute of Cardiovascular Diseases (NICVD), Dhaka. Subjects and methods: One thousand (1000) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(23 reference statements)
2
2
0
Order By: Relevance
“…Males had significantly higher LDL-C, TC, and TG levels, whereas HDL-C values were higher in female patients. Our findings are consistent with those of prior studies [39][40][41]. In contrast, previous studies in a Polish population showed that high LDL-C levels were significantly higher in females compared to males (P = 0.033); additionally, other lipid profile components were found to be less controlled in females than in males [42].…”
Section: Lipid Parameters At Admissionsupporting
confidence: 92%
See 1 more Smart Citation
“…Males had significantly higher LDL-C, TC, and TG levels, whereas HDL-C values were higher in female patients. Our findings are consistent with those of prior studies [39][40][41]. In contrast, previous studies in a Polish population showed that high LDL-C levels were significantly higher in females compared to males (P = 0.033); additionally, other lipid profile components were found to be less controlled in females than in males [42].…”
Section: Lipid Parameters At Admissionsupporting
confidence: 92%
“…Our research data show that the percentage of readmission among females was higher than that among males, a finding similar to that obtained in a study conducted in multiple centers worldwide that found a higher percentage of readmission in females than males [81]. A previous study showed that cardiovascular medications might have different effects on men and women because of variations in body composition, fluctuations in endogenous sex hormone levels (female monthly cycle and gestation), the pharmacokinetics/pharmacodynamics characteristics of some medicines, or the use of hormone replacement treatment or oral contraceptives [41,82].…”
Section: Hospital Outcomessupporting
confidence: 83%
“…The sample size of 96 was calculated based on the 63% prevalence of dyslipidemia in patients with ACS in the study conducted at another tertiary care hospital in Bangladesh with 15% permissible error. 8 Demographic features (age, gender) and cardiovascular risk factors [smoking: current or former, family history of CAD (first degree relatives such as siblings and parents usually aged <50 years {females} or <55 years {males}), hypertension: under medication, diabetes: random blood glucose ≥200mg/dl and/or under medication, reported dyslipidemia (under medication)] related data were recoded.…”
Section: Methodsmentioning
confidence: 99%
“…7 Dyslipidemia is an independent and modifiable risk factor that is common in our population. 8 It remains unrecognized until detected during the first presentation with ACS. So, this study aimed to find out the prevalence of dyslipidemia within 24 hours of admission with ACS and thereby help to the early classification of dyslipidemia and select the appropriate therapy.…”
mentioning
confidence: 99%